CASE REPORT OF IDIOPATHIC RETROPERITONEAL PELVIC SARCOMA INVADING THE SIGMOID MESOCOLON, OVARY, AND FALLOPIAN TUBE (Vietnam Journal of Community Medicine, 2026)
Retroperitoneal pelvic sarcoma is a rare malignant condition that often presents with nonspecific clinical manifestations and can be easily misdiagnosed as gynecological or gastrointestinal tumors. Preoperative diagnosis is challenging due to the paucity of symptoms and atypical imaging features. We report a case of idiopathic retroperitoneal pelvic sarcoma invading the sigmoid mesocolon, ovary, and fallopian tube in a 57-year-old female patient. The patient was evaluated using advanced imaging modalities and treated with wide surgical excision of the tumor together with the involved structures, achieving negative surgical margins. Histopathological examination confirmed the diagnosis of sarcoma, with features consistent with leiomyosarcoma. The treatment course highlights the pivotal role of radical surgical resection in achieving favorable outcomes. This case adds valuable data to the existing literature and underscores the importance of differential diagnosis and a multidisciplinary approach in the management of rare pelvic tumors.
Keywords: Sarcoma; retroperitoneal pelvis; sigmoid mesocolon; ovary; fallopian tube.